2014
DOI: 10.1177/000313481408001204
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Lower Extremity Anterior Compartment Syndrome in a Severely Hypothyroid Patient

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
1
1
Order By: Relevance
“…Hoffmann's syndrome is a rare condition, and to the best of the authors' knowledge it has not been previously reported in Scandinavia. Fasciotomy in this setting is even more extraordinary, with only a few published cases [1][2][3][4][5]. In contrast to previously published cases, the compartment that was affected in this case report was the dorsolateral compartment of the forearm, whereas the patients in previous reports all presented with compartment syndromes of tibial compartments.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Hoffmann's syndrome is a rare condition, and to the best of the authors' knowledge it has not been previously reported in Scandinavia. Fasciotomy in this setting is even more extraordinary, with only a few published cases [1][2][3][4][5]. In contrast to previously published cases, the compartment that was affected in this case report was the dorsolateral compartment of the forearm, whereas the patients in previous reports all presented with compartment syndromes of tibial compartments.…”
Section: Discussioncontrasting
confidence: 62%
“…The lower leg seems to be the most common location of compartment syndrome associated with hypothyroidism, with five previously published cases involving fasciotomy of tibial compartments [1][2][3][4][5]. To the best of our knowledge, only one patient with hypothyroid-induced compartment syndrome in the forearm has previously been reported.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest an increase in the volume of the compartment contents [7] which could lead to compartment syndrome. However, as mentioned above, Hoffmann's syndrome usually involves the gastrocnemius, whereas in our cases and all but one of the other case reports [6,[8][9][10][11][12] we found, the anterior and lateral muscles were predominantly involved. A connection between Hoffman's syndrome and compartment syndrome therefore seems unlikely.…”
Section: Discussionsupporting
confidence: 48%